Spatial variation in throughfall, soil, and plant water isotopes in a temperate forest. Issue 2 (12th December 2018) - Goldsmith, Gregory R.; Allen, Scott T.; Braun, Sabine; Engbersen, Nadine; González‐Quijano, Clara R.; Kirchner, James W.; Siegwolf, Rolf T.W.
Abstract: Studies of stable isotopes of water in the environment have been fundamental to advancing our understanding of how water moves through the soil–plant–atmosphere continuum; however, much of this research focuses on how water isotopes vary in time, rather than in space. We examined the spatial variation in the δ 18 O and δ 2 H of throughfall and bulk soil water, as well as branch xylem and bulk leaf water of Picea abies (Norway spruce) and Fagus sylvatica (beech), in a 1‐ha forest plot in the northern Alps of Switzerland. Means and ranges of water isotope ratios varied considerably among throughfall, soil, and xylem samples. Soil water isotope ratios were often poorly explained by soil characteristics and often not predictable from proximal samples. Branch xylem water isotope values varied less than either soil water or bulk leaf water. The isotopic range observed within an individual tree crown was often similar to that observed among different crowns. As a result of the heterogeneity in isotope ratios, inferences about the depth of plant root water uptake drawn from a two end‐member mixing model were highly sensitive to the soil sampling location. Our results clearly demonstrate that studies using water isotopes to infer root water uptake must explicitly consider how to characterize soil water, incorporating measures of both vertical and lateral variations. By accounting for this spatial variation and the processes that shape it, we can improve the application of water isotopes to studies of plant ecophysiology, ecohydrology, soil hydrology, and palaeoclimatology.